EXPLORING THE CHALLENGES ENCOUNTERED BY WOMEN WORKING IN LAW ENFORCEMENT AGENCY: A CASE STUDY OF DADU POLICE FORCE - Taniya Ahmed; Ghulam Mujtaba Malik; Nasir Mustafa; Hyder Ali Memon; Abdul Ahad Abro (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The current qualitative study was aimed to investigate challenges faced by female police officers through in-depth interviews, with a total of (24) interviews performed with lower ranking female police officers from the Dadu police force. The police officers were selected using a procedure that involved purposeful sampling. In addition, the data collected was examined using a thematic approach, which resulted in the development of (02) primary themes and (07) sub-themes. According to the data, it was discovered that the majority of female officers face a variety of challenges, such as gender bias and discrimination, inadequate training and resources, lack of career guidance, limited facilities, difficulty obtaining trust and cooperation from the community, and difficulty balancing pregnancy, maternity leave, and the responsibilities of caring for children. In addition, the findings of the study have been the impetus for the development of several recommendations that are meant to address these problems. In order to solve these problems, extensive actions need to be taken to create an atmosphere that is more inclusive and equal. This will make it possible for female officers to thrive and make contributions that are relevant to their profession.